Spirit Manusa Yaja dan Menyama braya Sebagai Etika Sosial Masyarakat Hindu Bali - I Nyoman Miarta Putra (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Awareness of Hindus performing ceremonies Hindus performing manusa yajna ceremonies en masse has increased. The splendor of the manusa yajna ceremony and menyama braya in the form of a ceremony is not accompanied by the spirit of carrying out manusa yajna in terms of improving the quality of Hindus, which in fact is also part of the implementation of manusa yajna. Improving the quality of humans in the spiritual aspect is an important thing. This can be used as a strengthening of Hindus as preservers of customs and culture. Overcoming this, Hinduism has social ethics as a form of concern for fellow people who live in the midst of traditional villages that are imbued with the spirit of Hindu religious teachings. Therefore the idealism of manusa yaja and menyama braya does not want fellow Hindus in particular and the wider community in general to be in trouble or suffering. Keywords: Manusa Yaja, Menyama braya, Social Ethics